A green catalyst-free concomitant air oxidation of DMSO and cumene to form methylsulfonylmethane (dimethylsulfone). (4th March 2022) - Li, Xiaolong; Deng, Youer; Zhao, Zhiying; Liu, Yachun; Zhang, Chao; Fu, Zaihui
Abstract : Methylsulfonylmethane (MSM) is a newly discovered human nutrient that has significant health care and therapeutic function. In this work, we developed a new type of catalyst-free air oxidation of dimethyl sulfoxide (DMSO) to MSM under relatively mild conditions based on the mechanism of isopropylphenyl free radicals (R·) activating molecular oxygen (O2 ) generating reactive oxygen species (ROS). Experimental results showed that cumene as a solvent, due to its active tertiary sp 3 C–H bond, promotes the efficient catalyst-free air oxidation of DMSO to MSM under relatively mild optimized conditions. Based on the quenching test of free radicals and theoretical calculation of the activation energies of two oxidation pathways of isopropylphenyl peroxy radicals (ROO·) and cumene hydroperoxide (CHP), it has been demonstrated that ROS in this reaction is mainly ROO· and hydroxyl radicals (HO·). Furthermore, we proposed a possible catalyst-free air oxidation mechanism. This work provided a simple and cost-efficient approach for the green synthesis of MSM. GRAPHICAL ABSTRACT: UF0001